Bioaccumulation and Elimination of Ivermectin by Eisenia foetida (Savigny 1826) Earthworms - Iglesias, Lucía Emilia (2023)
Purpose: Bovine and equine faeces are commonly used to produce vermicompost of Eisenia foetida earthworms as a soil fertility enhancer. In animal health, ivermectin (IVM) is frequently used for parasite control. However, IVM is eliminated mainly by faeces, which raises environmental concerns. Little is known about the transfer of IVM by the earthworms´ activity. In this work the accumulation of IVM in E. foetida worms cultured in vermicompost containing IVM and the ability of the worms to release IVM to a drug-free substrate were evaluated.Methodology: The acute toxicity test (72 h) of IVM and two bioassays, accumulation (A) and elimination (B), with E. foetida earthworms were performed in the current work. In A, the vermicompost produced was a mixture of equine and bovine faeces, the latter added with IVM 3,000 ng/g. Worms and substrates were sampled between 1 and 28 days post treatment (dpt). In B, worms obtained at 28 dpt in A were transferred to a substrate without IVM and sampled between 1 and 14 days later. Samples of worms and substrates were analysed using High Performance Liquid Chromatography (HPLC).Findings: There was no worm mortality in the toxicity test. In assay A, E. foetida worms bio-accumulated up to 26.8% of the IVM present in the substrate. When worms from assay A, were moved to IVM-free substrate, they released 84% of the bio-accumulated IVM during the first day.Recommendations: This study highlights that IVM bio- accumulated by earthworms and releasing in residue-free substrates represents a contamination risk, especially in farms that are minimising the use of chemical compounds.